FAST: Secure and High Performance Format-Preserving Encryption and Tokenization - Durak, Betül; Horst, Henning; Horst, Michael; Vaudenay, Serge (ASIACRYPT, 2021)
We propose a new construction for format-preserving encryption. Our design provides the flexibility for use in format-preserving encryption (FPE) and for static table-driven tokenization. Our algorithm is a substitution-permutation network based on random Sboxes. Using pseudorandom generators and pseudorandom functions, we prove a strong adaptive security based on the super-pseudorandom permutation assumption of our core design. We obtain empirical parameters to reach this assumption. We suggest parameters for quantum security.